A Common Stem Cell for Murine Cortical and Medullary Thymic Epithelial Cells? - Röpke, Carsten (Hindawi Publishing Corporation, 1995)
We have addressed the question whether the epithelial stroma in the thymus is derived from a common stem cell or whether cortical and medullary epithelial cells are derived from different embryonic stem cells emerging, for example, from endoderm and ectoderm. By the use of rapidly expanding cultures of thymic epithelial cells (TEC) from 14 to 16 day-old murine fetuses and by specific antibodies against cortical and medullary epithelium, respectively, we were able to demonstrate a small subpopulation of double-labeled TEC in the cultures. These cells were not present in TEC cultures initiated from thymuses of neonatal mice. Double-labeled TEC were also found in tissue sections from fetal thymuses. These findings may indicate that TEC populations of the cortex and the medulla are derived from a common stem cell, with potential for differentiation toward both cortical and medullary TEC.